Platelet Mobilization Induced by PAF and Its Role in the Thrombocytosis Triggered by Adrenaline in Rats - Castro-Faria-Neto, Hugo C; Bozza, Patricia T; Martins, Marco A; Dias, Paulo M F L; Silva, Patricia M R; Cordeiro, Renato S B (Thrombosis and Haemostasis, 1989)
The injection of PAP (6 μg/kg, i. v.) induced, in rats, haemoconcentration accompanied by an increase in the platelet number, as attested by the counts of platelets in blood samples diluted in formalin-free EDTA solution. This increase was significant at 15 min, peaked from 1 to 4 h and returned to basal levels 24 h after the lipid administration. The release of platelets induced by PAP was inhibited dose-dependently by specific PAP receptor antagonists such as WEB 2086 (0.5-2 mg/kg), BN 52021 and 48740 RP (5-25 mg/kg). Furthermore, platelet mobilization was clearly impaired in splenectomized animals stimulated by PAP, whereas thrombocytopenia and haemoconcentration by the same stimulus were intact. It was also noted that a second injection of PAP, 24 h after the initial stimulation with the lipid, failed to induce an increase in platelet counts, indicating autodesensitization. Desensitization to PAP or pretreatment with PAP antagonists clearly prevented the increase in the platelet counts after stimulation by adrenaline (15 μg/kg). These findings suggest that, in rats, PAP can induce release of platelets by a spleen-dependent mechanism and that this lipid may be relevant to the thrombocytosis triggered by adrenaline.
Keywords: PAF-acether (PAF); Thrombocytosis; Adrenaline; Spleen